2015
DOI: 10.1002/ppsc.201400214
|View full text |Cite
|
Sign up to set email alerts
|

Organometal Halide Perovskites: Bulk Low-Dimension Materials and Nanoparticles

Abstract: Organometal halide perovskites (hybrid perovskites) contain an anionic metal-halogen-semiconducting framework and charge-compensating organic cations. As hybrid materials, they combine useful properties of both organic and inorganic materials, such as plastic mechanical properties and good electronic mobility related to organic and inorganic material, respectively. They are prepared from abundant and low cost starting compounds. The perovskite stoichiometry is associated with the dimensionality of its inorgani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
155
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(156 citation statements)
references
References 90 publications
1
155
0
Order By: Relevance
“…This also constituted the first report on the preparation of luminescent perovskite NCs. The first solution-based synthesis of colloidal MAPbBr 3 NCs was carried out by the Pérez-Prieto and colleagues, 30 who employed medium-length alkyl chain organic ammonium cations, octylammonium bromide and octadecylammonium bromide as capping ligands to obtain luminescent NCs via the solvent-induced reprecipitation method. The role of these ligands was to provide a self-termination of the crystallization, leading to the formation of discrete nanoparticles in solution.…”
Section: Synthesis Of Perovskite Ncsmentioning
confidence: 99%
See 4 more Smart Citations
“…This also constituted the first report on the preparation of luminescent perovskite NCs. The first solution-based synthesis of colloidal MAPbBr 3 NCs was carried out by the Pérez-Prieto and colleagues, 30 who employed medium-length alkyl chain organic ammonium cations, octylammonium bromide and octadecylammonium bromide as capping ligands to obtain luminescent NCs via the solvent-induced reprecipitation method. The role of these ligands was to provide a self-termination of the crystallization, leading to the formation of discrete nanoparticles in solution.…”
Section: Synthesis Of Perovskite Ncsmentioning
confidence: 99%
“…They claimed that the excitonic-like features previously attributed to quantum confinement in spherical MAPbBr 3 nanoparticles were in fact a property of the nanoplatelets with decremental thickness, down to a single unit cell. They found that the absorption peak of their perovskite NC dispersion was blue-shifted by 0.5 eV with respect to the absorption onset of the bulk MAPbBr 3 . The fact that absorption and PL emission maxima were separated by 100 nm indicated that the dispersions were not phase pure, but rather consisted of nanoplatelets of varying thickness, where near-field energy transfer and reabsorption led to this large energetic separation.…”
Section: Synthesis Of Perovskite Ncsmentioning
confidence: 99%
See 3 more Smart Citations